A new species of Chaetopelma Ausserer, 1871 (Araneae, Theraphosidae) from Iran - Zamani Alireza; West Rick C. (Pensoft Publishers, 2025)
New data on the tarantula genus Chaetopelma Ausserer, 1871 are provided. A new species, Ch. persianum sp. nov., is described based on a single female specimen collected in northwestern Iran, which represents the easternmost record of the genus within its entire known range. Additionally, the correct publication date of Ch. olivaceum C.L. Koch, 1842 is discussed, and the known distribution records of all Chaetopelma species are mapped.